2013
DOI: 10.1177/0004563213497928
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohyperkalaemia in leukaemic patients: the effect of test tube type and form of transport to the laboratory

Abstract: Background: The present study was aimed at determining the effect of the tube type used for primary sample collection and the manner of transport prior to assessment (either manual or by pneumatic tube) on the degree of pseudohyperkalaemia in leukaemic patients. Methods: Blood from six leukaemic patients was collected into seven primary sample tubes (Monovette Õ , Sarstedt): sample A, heparinized blood gas syringe (potassium reference value); sample B, plasma Li-heparin without separator gel; sample C, plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…WBC count errors in PTS may be affected by fragile leukocyte membranes. Dastych et al showed that leukemia causes pseudohyperkalemia and was associated with in vitro cellular lysis [ 8 ]. Other research has considered how the PTS affects leukemic cells physically [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBC count errors in PTS may be affected by fragile leukocyte membranes. Dastych et al showed that leukemia causes pseudohyperkalemia and was associated with in vitro cellular lysis [ 8 ]. Other research has considered how the PTS affects leukemic cells physically [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, PTS transportation is also associated with some risks, such as in vitro hemolysis and aberrant results for plasma lactate dehydrogenase (LD) [ 6 , 7 ]. These errors are particularly more likely for leukemic patients with fragile leukocyte membranes [ 8 ]. The PTS effects are associated with transportation speed, acceleration and deceleration, spin times at corners, distance to station, and a lack of cushioning [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudohyperkalemia can be confirmed by determining plasma potassium in vacuum tubes with lithium heparin after centrifugation, and/or by whole blood potassium determination in electrolyte balanced lithium heparin syringe ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Cell membrane damage and lysis can also be influenced by the type of sample and the choice of phlebotomy site and/or method. 1 However, susceptibility to PTS-induced cell lysis varies significantly from one individual to another. 2 The results of the present study suggest that PTS interference with LD assays can be reduced through gentle aspiration of the blood into the tube and (to a lesser extent) use of adequate cushioning.…”
Section: Introductionmentioning
confidence: 99%
“…However, PTS transportation of blood specimens is known to be associated with aberrant assay results for plasma lactate dehydrogenase (LD), due to the mechanical disruption of blood cells. This bias is particularly problematical for leukaemic patients with fragile leukocyte membranes 1 but is not absent in subjects with normal blood cells. 2 The PTS’s effects increase with transportation speed, rapid acceleration and deceleration when changing in direction, transportation distance and a lack of cushioning.…”
Section: Introductionmentioning
confidence: 99%